Editorial: Wearable Robots and Sensorimotor Interfaces: Augmentation, Rehabilitation, Assistance or Substitution of Human Sensorimotor Function - Rose, Chad G.; Gan, Dongming; Hussain, Irfan (Frontiers in neurorobotics, 2022)
[...]Weiner et al. developed a prosthetic hand capable of semi-autonomous grasping, relying on a multi-modal sensor network combined with adaptive underactuated mechanisms. [...]with a focus on rehabiliation instead of augmentation or prosthetics, Topini et al. proposed an admittance controller for use in VR training environments, and examined its performance in a single subject pilot. [...]at the risk of understatement, the future work is dependent on continued advancement in the miniaturization, proliferation, and optimization of the requisite mechatronic subsystems.